Inovasi Wahana Swing: Membangkitkan Gairah Wisata Di Desa Selotapak, Trawas - Mojokerto - Setyaningrum, Idfi; Rashad Edy Kusuma, Bryan; Putri Radjamin, irzameingindra (LOSARI DIGITAL, 2023)
Tourism village development has emerged as one of Indonesia's regional economic growth strategies. Selotapak Village is one of the settlements that is utilizing Gartenhutte's natural tourism potential as its main appeal. Because the available facilities are currently limited, there is a need to increase the attractions that can attract tourists, one of which is the building of a one-of-a-kind swing. This attraction is ideal for the scenic scenery as well as the tourism environment. Certainly, the introduction of this new attraction will have a multiplier effect on tourism development and community well-being. The development of the